2019
DOI: 10.1371/journal.pone.0219611
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of intensity-modulated radiation therapy versus 2D-RT for the treatment of nasopharyngeal carcinoma: A systematic review and meta-analysis

Abstract: Background At present, the management of nasopharyngeal carcinoma (NPC) is mainly based on radiotherapy, but there are many radiation delivery techniques such as intensity-modulated radiotherapy (IMRT) and 2-dimensional radiotherapy (2D-RT). Materials and methods We searched all the eligible studies through the PubMed, Cochrane Library, Medline, and Embase. The endpoint events in meta-analysis were overall survival (OS), tumor local control including local-regional free… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
43
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(48 citation statements)
references
References 42 publications
0
43
0
1
Order By: Relevance
“…These values were significantly higher than those in the conventional radiation therapy group (23). In a meta-analysis, including 13,304 patients with NPC, Du et al (24), reported that the IMRT group was associated with a better 5-year OS (OR = 1.70; 95% CI = 1.36–2.12), tumor local control including local–regional free survival (OR = 2.08; 95% CI = 1.82–2.37), and progression-free survival (OR = 1.40; 95% CI = 1.26–1.56). IMRT is also associated with lower radiation toxicity, such as xerostomia, hearing loss, trismus and temporal lobe neuropathy.…”
Section: Discussionmentioning
confidence: 99%
“…These values were significantly higher than those in the conventional radiation therapy group (23). In a meta-analysis, including 13,304 patients with NPC, Du et al (24), reported that the IMRT group was associated with a better 5-year OS (OR = 1.70; 95% CI = 1.36–2.12), tumor local control including local–regional free survival (OR = 2.08; 95% CI = 1.82–2.37), and progression-free survival (OR = 1.40; 95% CI = 1.26–1.56). IMRT is also associated with lower radiation toxicity, such as xerostomia, hearing loss, trismus and temporal lobe neuropathy.…”
Section: Discussionmentioning
confidence: 99%
“…The role of chemotherapy regimens, proton therapy, and EBV-directed adjuvant therapy is still being evaluated [ 4 , 5 , 6 ]. Intensity-modulated radiotherapy (RT) has allowed precise targeting as well as a reduction in toxicity through sparing of normal tissue [ 7 , 8 , 9 , 10 ]. Due to the deep anatomic location and proximity to critical structures, treatment (TX) is still associated with toxicities [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the last 20 years, IMRT has allowed an increase in the dose of radiation applied to tumor lesions, while reducing radiotherapy-related toxicity to surrounding organs. Previous studies have shown that IMRT reduced the 5-year LRFS compared with conventional techniques, [ 5 7 ] and patients with NPC receiving IMRT had a 5-year overall survival (OS) of 75% to 83%, a DSS of 79% to 85%, a LRFS of 90% to 95%, and DMFS of 85% to 90%.…”
Section: Introductionmentioning
confidence: 99%